Relevansi Hukum Antara UU PSDN dan UU TNI dalam Pengelolaan Sumberdaya Manusia (Aspek Hukum Militer dan Kelembagaan Militer) - Nurwidya Kusma Wardhani; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to examine how the relevance or legal relationship between the National Resource Management Law and the Indonesian National Army Law. The relationship referred to here wants to examine the aspects of military law and military institutions. We know that after the issuance of the PSDN Law on October 24, 2019 there are several things regulated in it that are closely related to the TNI Law. Especially when talking about the human resources in it (for example the reserve component - komcad). The data collection method is carried out by studying literacy and laws and regulations and conducting qualitative descriptive data analysis to find out how the relationship between the PSDN Law and the TNI Law, especially for the management of human resources - komcad.